2010
DOI: 10.1063/1.3509416
|View full text |Cite
|
Sign up to set email alerts
|

Control of surface adatom kinetics for the growth of high-indium content InGaN throughout the miscibility gap

Abstract: The surface kinetics of InGaN alloys grown via metal-modulated epitaxy (MME) are explored in combination with transient reflection high-energy electron diffraction intensities. A method for monitoring and controlling indium segregation in situ is demonstrated. It is found that indium segregation is more accurately associated with the quantity of excess adsorbed metal, rather than the metal-rich growth regime in general. A modified form of MME is developed in which the excess metal dose is managed via shuttered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 29 publications
3
20
0
5
Order By: Relevance
“…In addition to p-type doping, MME has also been applied to the growth of high-indium-content InGaN throughout the miscibility gap [43], [44]. The InGaN films grown at solar-relevant compositions exhibit no phase separation or indium segregation, as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to p-type doping, MME has also been applied to the growth of high-indium-content InGaN throughout the miscibility gap [43], [44]. The InGaN films grown at solar-relevant compositions exhibit no phase separation or indium segregation, as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Michael Moseley's study revealed that indium surface segregation was more associated with the quantity of in− dium adsorbed on the surface, rather than growth in the In−rich regime in general [16]. He proposed a method for controlling indium surface segregation by shuttering Group− −III metal fluxes at a fixed modulation via metal−modulated epitaxy (MME).…”
Section: Improvement Of Crystal Qualitymentioning
confidence: 99%
“…While initial GaN buffer has been grown under the N-rich condition, Ga-rich condition has been maintained for final GaN to achieve a smoother surface for above quantum well layers [7]. InGaN with ~16 % of In mole fraction has been grown on GaN using metal-modulated epitaxy at 500 °C [8]. Temperature has been raised to 730 °C for the final growth of Al 0.25 Ga 0.75 N barrier with very thin GaN cap to avoid any possible ex-situ oxidation of AlGaN.…”
Section: Experimental Details 21 Epitaxial Growthmentioning
confidence: 99%